Catalytic performance of Au/ZnO nanocatalysts for CO oxidation
Au was loaded (1% wt.) on three different ZnO supports, by three different methods: photodeposition, double impregnation and ultrasonication. Two commercial ZnO supports were used, along with a ZnO. sample consisting of nanosized single crystals prepared by chemical vapour deposition. The samples were extensively characterised by various techniques. CO oxidation was used as a test reaction to compare the catalytic activity. The best results were obtained with ZnO prepared by chemical vapour deposition with Au loaded by ultrasonication that showed an activity of 2 mol(co) g(Au)(-1) h(-1) at room temperature. High-resolution electron microscopy images of the sample showed a number of gold nanocrystals epitaxially oriented on the ZnO rod. The unique catalyst-substrate interaction can be related to the increased catalytic activity of this sample, which was not observed for any of the others.